Gut Microbiome of an 11th Century A.D. Pre-Columbian Andean Mummy - Santiago-Rodriguez, Tasha M.; Fornaciari, Gino; Luciani, Stefania; Dowd, Scot E.; Toranzos, Gary A.; Marota, Isolina; Cano, Raul J. (PloS one, 2015)
The process of natural mummification is a rare and unique process from which little is known about the resulting microbial community structure. In the present study, we characterized the microbiome of paleofeces, and ascending, transverse and descending colon of an 11th century A.D. pre-Columbian Andean mummy by 16S rRNA gene high-throughput sequencing and metagenomics. Firmicutes were the most abundant bacterial group, with Clostridium spp. comprising up to 96.2% of the mummified gut, while Turicibacter spp. represented 89.2% of the bacteria identified in the paleofeces. Microbiome profile of the paleofeces was unique when compared to previously characterized coprolites that did not undergo natural mummification. We identified DNA sequences homologous to Clostridium botulinum, Trypanosoma cruzi and human papillomaviruses (HPVs). Unexpectedly, putative antibiotic-resistance genes including beta-lactamases, penicillin-binding proteins, resistance to fosfomycin, chloramphenicol, aminoglycosides, macrolides, sulfa, quinolones, tetracycline and vancomycin, and multi-drug transporters, were also identified. The presence of putative antibiotic-resistance genes suggests that resistance may not necessarily be associated with a selective pressure of antibiotics or contact with European cultures. Identification of pathogens and antibiotic-resistance genes in ancient human specimens will aid in the understanding of the evolution of pathogens as a way to treat and prevent diseases caused by bacteria, microbial eukaryotes and viruses.